Numerical study of a thermoacoustic refrigerator with different stack geometries - Murti, Prastowo; Dwi Astuti, Wijayanti; Febrinawarta, Burhan; Putra Pratama, Arief (Journal of Engineering and Applied Technology, 2025)
This study examines the performance of a thermoacoustic refrigerator with various stack geometries as a potential eco-friendly alternative to conventional refrigeration systems that rely on chlorofluorocarbons (CFCs). Thermoacoustic refrigerators create a cooling effect using sound waves and environmentally friendly gases such as helium. The stack, a crucial component where energy conversion occurs, must be optimized to maximize cooling efficiency. However, no studies have previously investigated the impact of stack geometries under a uniform system configuration. Thus, this study aims to numerically evaluate how different stack geometries and materials affect the performance of thermoacoustic refrigerators while maintaining consistent system geometry and properties to ensure fair comparison. The research focuses on three types of stack geometries: parallel plate, ceramic honeycomb, and wire mesh screen. Using DeltaEC software, the performance of these stacks was analyzed with a constant hydraulic radius. The results show that the wire mesh screen stack provides the highest cooling power (330 W) and coefficient of performance (COP) of 0.81, outperforming the other geometries. These findings highlight the potential of optimized stack designs to improve the efficiency of thermoacoustic refrigerators, promoting their development as a sustainable cooling technology.